ANATOMI HELAIAN DAUN MURRAYA SPP. (RUTACEAE) DI JAWA - Eka Fatmawati Tihurua; Inggit Puji Astuti; Rugayah Rugayah (BERITA BIOLOGI, 2012)
Leaf anatomy of four species of Murraya (Rutaceae) have been examined. Murraya spp. leaf has dorsiventral type. Anticlinal epidermis cell wall present with straight-undulate and square-irregular shaped. Anomocytic stomata distribute only in the lower surface and simple trichome spread in both leaf surfaces except M. crenulata (Turz.) Oliv. which has trichome only in the lower surface. Mesophyll consist of 2 or more layers of palisade tissues in the leaf upper part and sponge below, but M. exotica L. has palisade tissue in both leaf side. Oil gland distribute in the mesophyll. Crystal present as prismatic (cuboid) and drusse type.